Answer:
-5/4
Step-by-step explanation:
The average rate of change of f from x=0 to x=4 is_____.
This means we are being asked to evaluate [tex]\frac{f(4)-f(0)}{4-0}[/tex].
To do this we will need to find f(0) and f(4).
f(0) means what y-coordinate corresponds to x=0 on the curve. Find x=0, the curve is above there, go straight up and see y=5 there. This means f(0)=5.
f(4) means what y-coordinate corresponds to x=4 on the curve. Find x=4, then curve is above there, go straight up and see y=0 there. This means f(4)=0.
So we have:
[tex]\frac{f(4)-f(0)}{4-0}=\frac{0-5}{4-0}=\frac{-5}{4}[/tex].